The Dynamics in The Formation of Regional Products Of Law During Covid-19 Period in Central Java Province - Lita Tyesta ALW; Adissya Mega Christia (Jurnal Dinamika Hukum, 2021)
The policies issued by the central government in handling the impacts of Covid-19 are done through various laws and regulation.  These policies will be followed by the regional government policies through regional products of law including the Central Java Province Regional Government. This study analyzes how the Central Java Province Regional Government responds to the policies of the central government regulations so that the Covid-19 problem can be resolved properly. This research is done by normative juridical method with a statutory approach based on secondary data. The results of this study show that  Central Java Province Regional Government quickly and precisely formed various types of regional products of law based on the implementation of central government policies namely The Decree Of The Governor, The Instruction Of The Governor, The Instrunction Of Regional Secretary and various Circular Letters. Therefore, they are not the same as the usual regional regulation. Keywords: Covid-19; dynamics; regional products of law